Handbook of turbomachinery [2nd. ed. rev.] - Roy, Ramendra [ed.]; Logan, Earl [ed.] (Marcel Dekker New York, 2003)
Building on the success of its predecessor, Handbook of Turbomachinery, Second Edition presents new material on advances in fluid mechanics of turbomachinery, high-speed, rotating, and transient experiments, cooling challenges for constantly increasing gas temperatures, advanced experimental heat transfer and cooling effectiveness techniques, and propagation of wake and pressure disturbances. Completely revised and updated, it offers updated chapters on compressor design, rotor dynamics, and hydraulic turbines and features six new chapters on topics such as aerodynamic instability, flutter prediction, blade modeling in steam turbines, and multidisciplinary design optimization.
Keywords: Turbomachines -- Handbooks, manuals, etc